Constable & Toop - Jones, Gareth P. (Amulet Books, 2013)
Sam Toop has the ability to speak to ghosts, and is often asked by them to settle their unsettled affairs in the living world. His usual task is to give a loved one a message, or to change a will or two--but this time Sam is tasked with something more urgent: find out where the Black Rot came from, how and why it only affects ghosts, and stop it from wiping out the ghostly realm from all of London.